Zingiber officinale var. Rubrum Reduces the Rate of Prostaglandin Production - Fikri, Fauzan; Saptarini, Nyi M.; Levita, Jutti; Nawawi, Asari; Mutalib, Abdul; Ibrahim, Slamet (Pharmacology and Clinical Pharmacy Research)
In Indonesia, red ginger (Zingiber officinale var. Rubrum) is usually used as topical pain reducer by directly applying the fresh rhizome. The aim of this research was to provide information regarding the pharmacological activity of Z. officinale var. Rubrum rhizome infusion on the rate of prostaglandin production. The Z. officinale var. Rubrum rhizome used in this research was purchased from Research Institute for Spices and Medicinal Plants (Balittro) Manoko Lembang, West Java, Indonesia. This research was conducted by applying TMPD (N,N,Nâ,Nâ-tetramethyl-p-phenylendiamine) as the reagent. COX-1 and COX-2 enzyme inhibitory activity can be seen from TMPD chromogenic changes that occur during PGG2 reduction to PGH2. Phytochemical screening showed that flavonoid, quinone, and monoterpenoid/sesquiterpenoid were detected in both dried rhizomes and the water extract. Three spots were detected on thin-layer chromatography system which employing chloroform-methanol (5:5) as the eluent. The rate of prostaglandin formations either by Z. officinale var. Rubrum rhizome infusion or acetylsalicylic acid on COX-1 is slower (at 25th minutes) rather than COX-2 (5th minutes). We concluded that the rhizome of Z. officinale var. Rubrum reduces the rate of prostaglandin production. The rhizome of red ginger reduces the rate of prostaglandin production, which is slower in COX-1 than in COX-2. This plant could be further developed as anti-inflammatory drug candidate.Keywords: acetosal, antiinflammation, cyclooxygenase, NSAIDs, red ginger